Facing Frederick : the life of Frederick Douglass, a monumental American man - Bolden, Tonya (Abrams Books for Young Readers, 2018)
Examines the life and legacy of Frederick Douglass, the former slave who became an influential abolitionist, author, and speaker during the nineteenth century. Includes a timeline and photographs.